Fa‘āliyat Istikhdām al-Wasā’iṭ al-Ta‘līmīyah al-Sam‘īyah al-Baṣarīyah fī Ta‘līm Tamrīn al-Lughah al-‘Arabīyah - Amin, Ahmad Mustofa; Setiyadi, Alif Cahya; Najib, Ahmad Farhan Rif'an; Imron, Ali; Utomo, Wahyu Cahyo Budi (Universitas Negeri Jakarta, 2025)
The issue of low motivation and poor student performance in Arabic language learning remains a major challenge in many educational institutions. One contributing factor is the continued use of monotonous and minimally interactive teaching methods. This study aims to examine the effectiveness of interactive audio-visual learning media, particularly PowerPoint-based presentations, in enhancing students’ motivation and learning outcomes in language exercise (tamrīn al-lughah) lessons. The research was conducted in the 2025 academic year at the Islamic Modern Institute Darussalam Gontor, Ponorogo, using a quantitative approach and a quasi-experimental design. The study involved two groups: an experimental class that received instruction through audio-visual media, and a control class that followed conventional teaching methods. Statistical analysis using the Independent Samples T-Test showed a significant difference between the two groups. The experimental class achieved an average score of 8.48, while the control class only reached 6.32, with a significance value of 0.02 (< 0.05). These results indicate that interactive audio-visual media can significantly improve student engagement and comprehension in Arabic language learning. This study underscores the importance of pedagogical innovation, particularly the integration of multimedia tools, in creating a more dynamic and effective learning environment for foreign language acquisition.